2013
DOI: 10.1111/nure.12010
|View full text |Cite
|
Sign up to set email alerts
|

Dietary treatments for childhood constipation: efficacy of dietary fiber and whole grains

Abstract: Constipation in children is defined on the basis of several clusters of symptoms, and these symptoms are likely to persist into adulthood. The aim of this review article is to summarize the current literature on the use of dietary fiber and whole grains as treatments for childhood constipation. Current recommendations for fiber intake in children vary substantially among organizations, suggesting that the function of fiber in children is not fully understood. Additionally, no formal definition of "whole grain"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 63 publications
0
39
0
1
Order By: Relevance
“…Previous studies have suggested that unhealthy diets involving HHPD and low-fiber diet predisposed children to constipation [7, 17]. In this follow-up study, we endeavored to further explore the potential beneficial effect of EXQ on two constipated mice models, named HHPD model and HHPD + atropine model, which mimicked pediatric constipation due to HHPD and in combination with poor gastrointestinal mobility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that unhealthy diets involving HHPD and low-fiber diet predisposed children to constipation [7, 17]. In this follow-up study, we endeavored to further explore the potential beneficial effect of EXQ on two constipated mice models, named HHPD model and HHPD + atropine model, which mimicked pediatric constipation due to HHPD and in combination with poor gastrointestinal mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation may result of dietary, metabolic and painful anorectal condition; however, unhealthy dietary habits are most common cause in children [6, 7]. As the life quality improved, parents tend to seek refined and high-nutrition diets for their children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main components of natural plant foods are often different kinds of fiber [47À49]. Dietary fibers and whole grains have been used in treatment of childhood constipation as well [51]. Dietary fiber also increases the volume of the gut contents.…”
Section: Fibermentioning
confidence: 99%
“…Many studies had shown that SDF exhibited higher cholesterol‐ and sodiumcholate‐binding capacity (Nsor‐Atindana et al ., ), and it can be used to reduce blood pressure, prevent gastrointestinal problems and protect against several cancers, such as breast cancer, colorectal cancer and prostatic cancer (Chawla & Patil, ). It can also ameliorate constipation (Stewart & Schroeder, ), be taken as a partial substitution of lipid (De Moraes Crizel et al ., ) and has anti‐inflammatory activity on the digestive tract (Andoh et al ., ). In addition, DF has the antioxidant effect, especially in cereal which is rich in ferulic acid (FA), and it is related to the absorption of phenolic compounds, but the action of intestinal esterases on DF‐bound phenolic acid is facilitated on the SDF.…”
Section: Introductionmentioning
confidence: 99%